Analisis Literasi Keuangan pada Mahasiswa STAIN Teungku Dirundeng Meulaboh - Arroyyan Ramly; Fahlauddin Fahlauddin (STAIN Bengkalis, 2022)
This study aims to determine the financial literacy of STAIN Teungku Dirundeng Meulaboh students and the factors that affect financial literacy of STAIN Teungku Dirundeng Meulaboh students. This study uses a descriptive qualitative method. The number of respondents in this study is 150 students from 3 majors (Sharia and Islamic Economics, Tarbiyah and Teacher Training, and Da'wah and Islamic communication). The results of the study found that the financial literacy of students at STAIN Teungku Dirundeng Meulaboh is quite good, money statements and transactions shows the result of 90.5% (very good), financial planning and management found a rate of 70% (quite good), risks and benefits is 96.63% (very good), financial landscape is 49.65% (good), the knowledge of finance is 60% (good enough), and savings and loans 63.3% (good enough). In addition, there are four factors namely the gender factor, the parent's income factor, the age factor, and the parent's education level factor that affect the financial literacy of students at STAIN Teungku Dirundeng Meulaboh.